Synthesis of Some New Pyrazoline Derivatives and Related Compounds from Chalcones and their Antibacterial Activity - Naik, V.R.; Naik, H.B. (Asian Journal of Chemistry, 2010)
Chalcones on condensation with hydrazine hydrate in ethanol gave 2-pyrazoline which were converted to acetyl, benzyl, p-acetanilide, sulphonyl and nitroso derivatives. These products have been characterised by spectral studies and screened for antibacterial activity.